Prerequisite for COVID-19 Prediction: A Review on Factors Affecting the Infection Rate - Tang S.G.H.; Hadi M.H.H.; Arsad S.R.; Ker P.J.; Ramanathan S.; Afandi N.A.M.; Afzal M.M.; Yaw M.W.; Krishnan P.S.; Chen C.P.; Tiong S.K. (MDPI, 2023)
COVID-19; disease incidence; epidemic; health policy; infectious disease; policy implementation; socioeconomic status; vaccination; air conditioning; coronavirus disease 2019; COVID-19 testing; host; human; infection rate; infection risk; meteorological phenomena; nonhuman; prediction; Review; Severe acute respiratory syndrome coronavirus 2; social distancing; socioeconomics; vaccination; diagnosis; epidemiology; mask; COVID-19; COVID-19 Testing; Humans; Masks; SARS-CoV-2